The Impact of Incumbency on Turnout: Evidence from Italian Municipalities - Marco Alberto De Benedetto; Maria De Paola (Institute for the Study of Labor (IZA), 2013)
We analyze how having an incumbent among candidates affects electoral turnout. We use a rich data set providing information on the electoral results of Italian municipal elections over the period 1993-2011. Endogeneity issues are handled through an instrumental variable approach using the mayor term-limit as an instrument for the presence of the incumbent mayor among candidates. Controlling for electoral competition, we find that the impact of incumbency is heterogeneous across geographical areas: incumbency increases turnout in the South of Italy, whereas we do not find any statistically significant effect in the North. As the positive effect holds true only for southern municipalities endowed with low levels of social capital we speculate that this is the result of incumbent politicians using their resources to establish clienteles.
Keywords: D72; D78; J71; J16; 330; incumbency; political participation; electoral turnout; social capital